The Efficacy and Safety of Fecal Microbiota Transplantation Combined With Biofeedback for Mixed Constipation: A Retrospective Cohort Study - Yang, Bo; Tian, Hongliang; Ye, Chen; Lin, Zhiliang; Zhao, Di; Ma, Chunlian; Zhao, Jiangman; Wu, Shouxin; Jiang, Rongfeng; Li, Ning; Qin, Huanlong; Chen, Qiyi (Frontiers in Medicine, 2021)
This study aims to assess the effectiveness and safety of fecal microbiota transplantation (FMT) combined with biofeedback for patients with mixed constipation. Patients who received biofeedback (biofeedback group, n = 40) and those who received FMT combined with biofeedback (FMT combination group, n = 45) were enrolled. Spontaneous bowel movements (SBMs) frequency, Bristol Stool Form Scale (BSFS), and Patient Assessment of Constipation Symptoms (PAC-SYM) score were analyzed to evaluate the effect of treatment. Gastrointestinal Quality of Life Index (GIQLI) scores of patients were used to assess the quality of life, and the safety of FMT combination therapy was evaluated by the presence of adverse events. The 16S rRNA gene sequencing was performed on the fecal samples of 12 donors, feces of 31 patients before and after receiving FMT combination treatment. Comparing the biofeedback group and the FMT combination group 1 month after the treatment, significant differences were observed in the mean value of SBM frequency, BSFS, and PAC-SYM scores, which were 2.15 ± 1.05 vs. 3.61 ± 0.89 (p = 0.0031), 2.1 ± 0.9 vs. 2.5 ± 1.2 (p = 0.008), and 2.4 ± 0.5 vs. 2.2 ± 0.6 (p = 0.0021), respectively. Meanwhile, FMT combination therapy had long-term beneficial effects according to the data collected at six months and 12 months after the treatment. With respect to the quality of life, GIQLI scores were higher in the FMT combination group (103.6 ± 15.1) compared with that in the biofeedback group (88.7 ± 10.1) one month after administration (p = 0.0042). In addition, there were no significant differences between the two groups in adverse events, including abdominal pain, diarrhea, dizziness, nausea, vomiting, and other side effects. Results of 16S rRNA gene sequencing showing some well-known probiotics had significantly increased after FMT combination treatment compared with pre-FMT samples, such as Prevotella and Bifidobacterium. Findings of this study suggested that FMT combined with biofeedback could be effective and safe for patients with mixed constipation.